2012
DOI: 10.1021/ol3016435
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Sequential Ullmann N-Arylation and Aerobic Oxidative C–H Amination: A Convenient Route to Indolo[1,2-c]quinazoline Derivatives

Abstract: An efficient synthesis of indolo[1,2-c]quinazoline derivatives has been developed by copper-catalyzed sequential Ullmann N-arylation and aerobic oxidative C-H amination. The protocol uses readily available 2-(2-halophenyl)-1H-indoles and (aryl)methanamines as the starting materials to afford indolo[1,2-c]quinazolines, which are the core units of hinckdentine A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(32 citation statements)
references
References 44 publications
0
30
0
Order By: Relevance
“…It raised attention from many chemists and became one of the focal point in organic chemistry research in recent years. Sang et al reported a copper-catalyzed sequential Ullmann N-arylation and aerobic oxidative C-H amination for the convenient synthesis of indolo[1,2-c]quinazoline derivatives [41]. In their research, 2-(2-halophenyl)-1H-indoles and (aryl)methanamines were adopted as raw materials to generate corresponding Schiff base via Ullmann reaction.…”
Section: Reviewmentioning
confidence: 99%
“…It raised attention from many chemists and became one of the focal point in organic chemistry research in recent years. Sang et al reported a copper-catalyzed sequential Ullmann N-arylation and aerobic oxidative C-H amination for the convenient synthesis of indolo[1,2-c]quinazoline derivatives [41]. In their research, 2-(2-halophenyl)-1H-indoles and (aryl)methanamines were adopted as raw materials to generate corresponding Schiff base via Ullmann reaction.…”
Section: Reviewmentioning
confidence: 99%
“…): Thermo Scientific Exactive spectrometer; in m/z. [4], and 2-(2-bromophenyl)-5-chloro-1H-indole (1g) [4] were prepared according to reported procedures. All other chemicals used in this study were commercially available.…”
Section: Experimental Partmentioning
confidence: 99%
“…It should be noted that, during our work, we became aware of a report on the elaboration of these 1H-indole derivatives to the synthesis of indolo[2,1-c]quinazolines by Zhang and co-workers. [4].…”
mentioning
confidence: 99%
“…A convenient and clean water-mediated synthesis of a series of indolo[1,2-c] quinazoline derivatives was reported using alternative nonconventional energy sources. The products are obtained in shorter times with excellent yields (78-89 %) from the MCR of 2-aminobenzimidazole, malononitrile, and carbonyl compounds [55]. In their research, 2-(2-halophenyl)-1H-indoles and (aryl)methanamines were adopted as raw materials to generate corresponding Schiff base via the Ullmann reaction.…”
Section: Water-mediated Quinazoline Synthesismentioning
confidence: 99%